A influência do REFIS 2009 na inadimplência dos contribuintes industriais do Estado do Ceará - análise de quebra estrutural - Moreira, Marcelo da Cunha (2014)
In an attempt to promote the settlement of claims and increase revenue, the government often has been using the program for the renegotiation of tax debts. From the year 2000 several programs subdivisions were created, associated with several financial benefits, such as discount in fines imposed, reduction in accrued interest, and lower rates for future installments, generating an increase in the amount of installments payable debt. The fierce competition among states for business investment, better known as "Tax War" is another factor that justifies the granting of tax benefits, disregarding the economic logic and the law. The lack of transparency of outstanding debt and the amount of the tax waiver undermines the analysis of efficiency, efficacy and effectiveness in the allocation of resources. This paper analyzes the influence of Refis 2009 State of Ceará defaults by taxpayers in the manufacturing industry. To this end, an econometric model that estimates, by the method of least squares the occurrence of "structural break" in the credits entered curve outstanding debt of Ceará industrial taxpayers who joined the program in the period before and after 2009 was s . the result points to the "structural break" in May 2011 at two of the four sectors of the manufacturing industry analyzed, the same occurring in the analysis of the sectors together. However, no conclusive influence on Refis "structural break".